An ethnic ethnographic review: The kinship system of the Dayak Ribun tribe in West Kalimantan: - Arkanudin, Arkanudin; Rupita, Rupita; Batuallo, Ignasia Debbye (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
This research aims to explore the kinship system of the Dayak Ribun tribe in West Kalimantan. It uses the kinship system tree to visualize the relationship roots. This effort is also based on the refinement of the tree that has existed in the past. Moreover, the method used is an ethnographic approach, where data collection is carried out explicitly using observation, in-depth interviews, and live-in. Ethnic ethnography is gathering a variety of information from its source. According to the results, the kinship system in the Dayak Ribun community is bilateral, that is, relations through two family lineages, both sides of the mother or wife and father or husband. The principle of heredity is bilateral, where the responsibilities of husband and wife are the same in the family, both in children's education and in controlling the family economy. The marriage of a family member who is still a descendant from both the father and the mother is strictly prohibited, which is only allowed to marry between cousins ​​three times. In the distribution of inheritance, there is no difference between sons and daughters. Still, there are differences in some instances, especially for those who remain with their parents. They will get a higher share because they are responsible for their parents' old age until they die.